From Anti-Corruption to Economics: An Extension of Tsai et al. (2021) - Joseph Bonneau (Institute for Replication (I4R), 2022)
Tsai, Trinh, & Liu (2021) in their initial study sought to examine whether anticorruption efforts in authoritarian regimes affected public opinion of these regimes through not just direct effects, but also indirect effects through affecting evaluations of competence and morality. Conducting a con-joint study in China where respondents were asked to choose between two potential local officials, Tsai et al. found that 26% of the total effect of these officials punishing corrupt subordinates was estimated to come through indirect effects that go through evaluations of morality and compe-tence. Using their code, I reproduced their original findings, and did not find any notable coding errors while doing so. Then, taking advantage of the fact that Tsai et al. included several additional covariates beyond punishment in their experiment, I engaged in an extension of the original model, using the same method, to examine whether economic performance characteristics have indirect effects on evaluation through competence and morality as well. I found results that sug-gest that economic performance does have an indirect effect on preferences through competence and morality. I then tested the robustness of Tsai et al.'s original heterogeneous sensitivity tests by varying cut points on two demographic variables and found that their findings of a lack of heterogeneous sensitivity remain robust to different cut-points. In all, my efforts suggest that Tsai et al.'s methods are valid and their findings robust.
Keywords: 330